USE OF INFORMATIVELY-COMMUNICATION TECHNOLOGIES IN TEACHING OF FOREIGN LANGUAGES MIXED LEARNING AS OPTIMAL AND EFFECTIVE FORM OF MODERN EDUCATION - Желуденко, М. А.; Сабітова, А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article is dedicated to mixed learning as an optimized form of today education, the basis of modernization which prospective vector of development presupposes application of information and communication technologies. The article considers the possibilities of using modern information and communication technologies in the process of learning foreign languages in order to improve education quality through rational workload planning, selection of correspondent training material and monitoring of acquired knowledge; studies the experience of introducing e-learning, its advantages and disadvantages; analyzes the peculiarities of the use of electronic teaching aids during in-class activities and as the means of individual independent work; defines the specific features and necessary conditions for applying mixed learning; specifies definitions of the terms ’e-learning’, ’mixed learning’, and ’distance learning’, and also defines terminological options for the definition of the notion of mixed learning; determines the range of issues regarding development of mixed learning models; describes main characteristics of mixed learning (flexibility, mobility, availability). The authors discuss positions of modern specialists concerning the use of information technology in teaching foreign languages, well as introduce their own examples of the implementation of mixed learning in the training process; explore the practical aspect of using Deutsche Welle information Internet resource while teaching German as the second foreign language at the National Aviation University; emphasize the role of a teacher as an individual consultant in the process of acquiring knowledge through implementing elements of mixed learning. Furthermore, the authors define further directions of development and implementation of mixed learning and e-learning, state the necessity of developing academic complexes and renovating curricula with elements of mixed learning.